2008
DOI: 10.1016/j.exer.2008.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin-1 mediated regulation of extracellular matrix collagens in cells of human lamina cribrosa

Abstract: Endothelin-1(ET-1), a potent vaso-active peptide, mediates extracellular matrix regulation resulting in an increase in collagen deposition in various cell types and tissues and has been proposed to play a key role in glaucoma pathology. The role of ET-1 in the regulation of extracellular matrix collagens at the level of optic nerve head is not known. In this study we have examined the role of ET-1 in extracellular matrix collagen regulation in primary cultures of human lamina cribrosa cells. Our hypothesis is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 70 publications
(83 reference statements)
0
13
0
4
Order By: Relevance
“…22 Interestingly, ET-1, which has been shown to be up-regulated during glaucoma, also enhances expression of MMP-2, which further mediates a concentration-dependant increase of collagen type I alpha 1 and collagen type VI alpha 1 production through stimulation of lamina cribrosa cells. 23,62,75 Because collagen induction is a marker of tissue fibrosis, this may lead to RGC death. Collagen up-regulation may lead to compromised astrocyte function and thereby secondarily RGC death.…”
Section: Increased Expression Of Matrix Metalloproteinases Resultsmentioning
confidence: 99%
“…22 Interestingly, ET-1, which has been shown to be up-regulated during glaucoma, also enhances expression of MMP-2, which further mediates a concentration-dependant increase of collagen type I alpha 1 and collagen type VI alpha 1 production through stimulation of lamina cribrosa cells. 23,62,75 Because collagen induction is a marker of tissue fibrosis, this may lead to RGC death. Collagen up-regulation may lead to compromised astrocyte function and thereby secondarily RGC death.…”
Section: Increased Expression Of Matrix Metalloproteinases Resultsmentioning
confidence: 99%
“…ET-1 has also been found to contribute to the disruption of anterograde axonal transport, another key area of impairment in glaucomatous eyes [50,51]. Interestingly, one study found that ET-1, acting through activation of both ET A and ET B , caused increases in collagen synthesis in lamina cribrosa (LC) cells, suggesting that ET-1 mediates ECM remodeling at the level of the ONH, possibly contributing to increased collagen deposition, reduced aqueous humor outflow and progressive damage to the ONH [52]. In a study on rabbits, intravitreal injection of ET-1 resulted in significant elevation of synthesis of NO, a potent substance known to cause oxidative damage to the ONH [53].…”
Section: Good and Kahookmentioning
confidence: 98%
“…While endothelin has been proposed to be a model of ischemic optic neuropathy in a variety of species (Chauhan et al, 2004; Cioffi et al, 1995; Orgul et al, 1996a; Orgul et al, 1996b), a robust literature has called into question its actual mechanisms (He et al, 2007; Murphy et al, 2010; Rao et al, 2008; Stokely et al, 2002; Wang et al, 2008; Yorio et al, 2002)and there are no definitive studies that establish the “glaucomatous” nature of the neuropathy (Chauhan et al, 2004; Oku et al, 1999). One paper has reported the “glaucomatous” loss of retinal ganglion cells in rats following systemic exposure to retinal heat shock proteins, but documentation of the “glaucomatous” nature of the neuropathy has not been provided (Wax et al, 2008).…”
Section: Future Directionsmentioning
confidence: 99%